Membangun Kembali Social Capital Dalam Rangka Reformasi Administrasi di Indonesia - SRI Juni Woro Astuti (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Social capital is the public goods created by the community and owned by the community as well, not by individuals or government, nor by groups who have abundant resources. Social capital is formed by itself in a relatively long period of time, as well as the formation of value systems or culture in general. Therefore, when social capital has been formed, it will be hard to break away (unlike financial capital). By applying high ethical standards in public service, the social capital which is slowly fading will bounce back by itself. But it's certainly not easy. It takes commitment and integrity of government administrators to actually apply these ethical standards with a consistent and adequate legal system to provide a deterrent effect for those who break them. Economic emphasis on public sector change puts a high value on what is regarded as something that can not be avoided, namely the good of private models in managing the organization, described as a "more productive", which are different approaches to public services commonly referred to as bureaucratic.